Multiport Bidirectional DC-DC Converter for Electric Vehicle - Kundu, Upasana; Tiwari, Shailesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Nowadays, dc-dc converter is used as power electronic interface in various application such as electric vehicle. In this project, a multiport dc-dc converter will be designed to interface from renewable energy sources such as solar, energy storage system as battery and ultracapacitor. The main characteristics of this proposed converter is its ability to handle diversified energy sources with different voltage and current characteristics. Then dc-ac converter is used to interface between dc link and traction motor as induction motor. The four-port bidirectional buck boost converter will be designed to create an interface between source and load in a single stage conversion. This proposed single stage converter can be operated in buck, boost and buck-boost mode. This is a 3:1 dc-dc converter which has three source namely solar, battery and supercapacitor and output load will be traction motor. The amount of power flow between the input and the output can be controlled by adjusting the duty cycle of the dc-dc converter.